PENGARUH KUALITAS PRODUK DAN CITRA MEREK TERHADAP MINAT MENGGUNAKAN ATM SETOR TUNAI BANK MANDIRI DI SEMARANG - Aulya Rachman; Bulan Prabawani (Universitas Diponegoro, 2016)
The research was distributed by the fast development of information technology so that the required means of banking transaction that can do anything to help the banking transaction of costumer activities. ATM Cash Deposit is one of the types of services offered by Mandiri Bank.The purpose of doing research is to know the influence of the variabel quality of product, and brand image against the interest in using ATM Cash Deposits Mandiri Bank. Its population is user indepent Bank ATM machine service. The sampel as many as 100 respondents with the sampling technique used was accidental sampling. The analysis of the data used in this research using SPSS 18.8 program, where do test validity, reliability, determination of the coefficient of the corelation coefficient, regression analysis, simple and simple and double, and the test of significance (t-test and F-test).The results of this study indicate that the variable product quality and brand image has a positive influence against the interest in using ATM Cash Deposits Mandiri Bank.The suggestions can be submitted is a good idea to improve the quality of the ATM Cash Deposits Mandiri Bank and keeping the brand image in order to be always trusted by customers.